PENGARUH PENERAPAN TEKNIK MNEMONIC TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS V SD INPRES 6/75 TA KABUPATEN BONE - Rukayah, Rukayah; Jafar, Muh. Idris; Yulianti, Lilis (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstract: Abstract: This research is a quantitative study with a One Group Pretest Posttest design aimed at determining the effect of applying Mnemonic techniques on the poetry writing ability of fifth-grade students at SD Inpres 6/75 TA, Bone Regency. This study involved 22 fifth-grade students as samples using the saturated sampling technique. The data collection technique was carried out through pretest and posttest poetry writing ability tests. Based on the results of descriptive statistical analysis, the average pretest score of the students was 42.0455, which falls into the